Model Penelitian Tafsir; Studi Karya Howard M. Federspiel : (Popular Indonesian Literature Of The Qur’an) - Badrut Tamam, Ahmad (MADINAH, 2018)
Study efforts on the Koran in Indonesia have been carried out from generation to generation and produce various interpretations and books on the study of the Koran. These works certainly have different characteristics with interpretations born in the place of origin of the Qur'an revealed. The difference is due to differences in space and time contexts and differences in language and cultural backgrounds. Therefore, this article will analyze how the development of the Qur'anic interpretation in Indonesia through the work of Howard M. Federspiel entitled "Popular Indonesian Literature of the Qur'an". The work is one model ofinterpretation research in Indonesia.